Impact Assessment and Management Challenges of Key Rural Human Health Infrastructure Under Sea Level Rise - Mitchell, Molly; Isdell, Robert E.; Herman, Julie; Tombleson, Christine (Frontiers in Marine Science, 2021)
Accelerating sea level rise in Virginia, United States, will significantly increase the flooding threat to low-lying roads, residences, and critical infrastructure as well as raise the water table, allowing saltwater intrusion into well water and threatening the function of septic fields. Although most of the adaptation work in Virginia has focused on urban economic centers, the majority of the coastline is rural and faces different threats and opportunities to address them compared to urban areas due to their reduced economic assets and their reliance on private infrastructure. In this case study, we assess the potential for geospatially quantifying impact to septic systems and adjacent water ways due to sea level rise. The case study found that the data necessary to reliably quantify these impacts on a state-wide scale are lacking and collection of that information needs to be prioritized given the potential for extensive sea level impacts.